Measurements and searches for new physics in diboson processes with the D0 detector - Ferapontov, Alexey V. (Kansas State University, 2009)
This dissertation describes a comprehensive study of the Zgamma [to] eegamma/mumugamma/nu[bar]nugamma process. The data have been collected with the D0 detector at the Fermilab Tevatron p[bar]p collider with the center-of-mass energy of 1.96 TeV, and correspond to up to 3.6 fb[superscript]-1 of integrated luminosity. Firstly, in this study we perform a measurement of the Zgamma production cross section. The measured cross sections in both llgamma (l = e or mu) and nu[bar]nugamma channels are the most precise cross sections measured at hadron colliders to date, and they agree within uncertainties with the theoretical calculations to the next-to-leading order. We claim the first observation of the Zgamma [to] nu[bar]nugamma process at hadron colliders at 5.1 standard deviations statistical significance. We also conduct a search for anomalous Zgamma processes. Such anomalous Zgamma processes, where a Z boson couples to a photon, result in an increased cross section and an enhancement of the production of high-energetic photons. Thus, an observation of this kind might possibly indicate the presence of new physics. Having found no excess of data over the SM expectations, we set the most restrictive 95% C.L. limits on the anomalous trilinear Zgammagamma and ZZgamma gauge couplings (ATGC) at hadron colliders to date: |h[subscript]30[superscript]gamma| < 0.033, |h[subscript]40[superscript]gamma| < 0.0017, |h[subscript]30[superscript]Z| < 0.033, and |h[subscript]40[superscript]Z| < 0.0017, which mark almost three times improvement over the most recent results published to date. Three out of four current limits improve on the LEP limits, and are the tightest limits on ATGC in the world. Finally, we performed a search for narrow vector and scalar resonances that decay to Zgamma. Many extensions of the SM predict such resonances, thus making this search a test of the gauge sector of the SM. We found no significant deviation of data from the SM predictions, and hence we set 95% C.L upper limits on the production cross section of the resonances.
Keywords: diboson; photon; anomalous; couplings; resonance; Physics, Elementary Particles and High Energy (0798)